Audience Reception: Prevention of Online Gambling Site Advertisements Within The Scope of Instagram - Jimmy, Muhammad Fathur Rachman; Sumarlan, Iman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The issue of online gambling advertisements proliferating on Instagram's platform is of significant concern and demands immediate attention. To curb this trend, Instagram must strengthen its measures against users who propagate these advertisements to discourage others from following suit and prevent them from appearing on the platform's timeline. Such deterrent measures must be implemented without delay to ensure Instagram's platform's continued integrity and safeguard its users from exposure to unwanted content. The present study employs qualitative reception analysis, and the findings underscore the need for Instagram to implement stringent measures to prevent the proliferation of online gambling advertisements on its platform. The imperative to preserve the intended purpose of social media and ensure a positive user experience necessitates that Instagram improves its reporting feature to regulate such ads more effectively. Taking a proactive approach will bolster the platform's efforts to promote social media's health and safeguard the interests of its users. By adopting a proactive approach, the researcher can implement various strategies and policies that will help enhance the platform's overall user experience. This may include improving content moderation, preventing the spread of misinformation and harmful content, and addressing technical issues. This approach will enable us to prioritize the safety and well-being of social media users by implementing more robust privacy and security measures and providing more comprehensive support for those experiencing online harassment or other forms of abuse. Through these efforts, we can build a more robust, more resilient platform that is better equipped to meet the evolving needs of its users.
Keywords: Online Gambling Advertisements; Content Moderation; User Experience; Privacy and Security